AI dalam Rekrutmen: Analisis terhadap Kecepatan, Efisiensi Waktu, Objektivitas Penilaian dan Risiko Kualitas - Utama, Zahera Mega; Rizki, Lutfi Nur; Suprakto, Reza Pratiknyo; Puspitarini, Lusie Prasetyawati (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The advancement of artificial intelligence (AI) has significantly transformed recruitment and employee selection processes. This study explores the use of AI in recruitment, focusing on speed, time efficiency, assessment objectivity, and the potential risks to candidate quality. Using a qualitative descriptive approach and literature review, this paper analyzes how AI is integrated into various stages of recruitment, including CV screening, chatbot-based interviews, and algorithm-driven candidate analysis. The findings indicate that AI can enhance recruitment efficiency and reduce the administrative burden on HR departments. However, it also presents challenges such as algorithmic bias, limitations in evaluating soft skills, and the risk of losing the human touch. Therefore, the most effective approach lies in combining AI systems with human HR professionals to ensure a recruitment process that is not only fast and objective but also accurate and focused on long-term quality.